Border Formation - Grazia Tona (A+BE: Architecture and the Built Environment)
This doctoral thesis examines the militarisation of the Southern border of Hungary as a process of spatial formation, expanding the debate on borders from the political to the architectural arena. Combining spatial theory with empirical research on the case study, the thesis rethinks the border as a complex spatial system, with an agency of its own. From this perspective, it contests the enforcement of spatial boundaries from the above and related ideas of fixity. It brings attention to the agency of space in the advancement of a material becoming; the role of migration in the radical redefinition of meanings and functions of space; and the action of technologies in the strategic manipulation of measures and scales. While conceptualising the border as a space in formation, this thesis builds a diagrammatic method of study and moves the research in an ontoepistemological direction. With the aim of fostering a change in those structures that control the partition and governance of space, this doctoral study calls the discipline of architecture to review its questions, methods, and practices. It invites to use architectural knowledge to engage with borders’ complexity and challenge their established meanings and makings.